1998
DOI: 10.1016/s0014-5793(98)00919-3
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis‐like, reversible changes in plasma membrane asymmetry and permeability, and transient modifications in mitochondrial membrane potential induced by curcumin in rat thymocytes

Abstract: Curcumin (diferuoylmethane) is a natural compound with anticareinogenic activities which is able to exert either proapoptotic or antiapoptotic effects in different cell types. This paper focuses on the sequence and extent of primary events induced by curcumin, in comparison with those occurring during dexamethasone-induced apoptosis in rat thymocytes. It also presents annexin VI-FITC as a new probe for studying membrane asymmetry. Curcumin readily penetrates into the cytoplasm, and is able to accumulate in mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
85
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 34 publications
8
85
0
Order By: Relevance
“…In addition, CUR in the medium (apical side) rapidly degraded ( Figure 9C). These results are similar to previous studies [40][41][42] and most likely occurred due to rapid cellular uptake of CUR from the medium and/or CUR degradation in the medium.…”
supporting
confidence: 92%
“…In addition, CUR in the medium (apical side) rapidly degraded ( Figure 9C). These results are similar to previous studies [40][41][42] and most likely occurred due to rapid cellular uptake of CUR from the medium and/or CUR degradation in the medium.…”
supporting
confidence: 92%
“…Similar observations were made during curcumin induced apoptosis in human leukemic cells [22]. Curcumin also increased the level of glutathione which would prevent thiol depletion occurring during apoptosis [6]. Thus the role of curcumin in redox balance needs further investigation.…”
Section: Discussionsupporting
confidence: 64%
“…Our results showed that there was no difference in membrane fatty acid composition between 7T and HEp-2 cells. We must point out that in our experiments we extracted lipids from whole cells, because curcumin can accumulate not only in plasma membrane, but also in membranes of endoplasmic reticulum and nuclear envelope (Jaruga et al, 1998). Therefore, we can not exclude some differences in fatty acid composition between membranes of different cell compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is a lipophilic compound, unstable in aqueous solutions (Wang et al, 1997), In the study on rat thymocytes it was shown that such properties enable this molecule to easily 14 14 enter the cell and localize in the membrane regions like: plasma membrane, membranes of endoplasmic reticulum and nuclear envelope (Jaruga et al, 1998). In one of the recent papers it was found that, except for membrane localization, minor nuclear localization occurred in mouse spleen lymphocytes, mouse fibroblast (NIH3T3), T cell lymphoma of murine origin (EL4) and breast cancer cell line of human origin (MCF7) (Kunwar et al, 2008).…”
Section: Discussionmentioning
confidence: 99%